Classification of skin cancer images using TensorFlow and inception v3 - Sai V, Bhavya; Rao G, Narasimha; M, Ramya; Sree Y, Sujana; T, Anuradha (International Journal of Engineering and Technology, 2018)
It is easy for a human eye to distinguish the images of similar appearance but classifying the images like that of cancer affected skin  requires more expertise. And as the skin cancer cases are increasing globally, it requires more number of human experts. To overcome this problem, many people are working on constructing machine learning classifiers which can detect skin cancer automatically by    classifying skin images. This paper concentrates on developing an approach for predicting skin cancer by classifying images using deep convolution neural network. The proposed work is tested on standard cancer dataset and obtained more than 85% accuracy.